Social Entrepreneur Model: Analysis of Muslim Women's Economic Empowerment Through Emping Crackers Industry in Tulungagung - Siti Kalimah; Sirajul Arifin; Riska Agustin; Riza Hafizi, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2025)
The role of women in the economic sector extends beyond the domestic sphere to include participation in business, employment, and public decision-making. However, many women continue to experience structural barriers such as gender discrimination and limited access to economic opportunities. This phenomenon is also evident in Ngadirejo, Tulungagung, where the emping-melinjo industry dominated by Muslim women faces challenges related to business competition, resource limitations, and sustainability. This study aims to analyze the economic empowerment of Muslim women in the emping industry using the Social Entrepreneurship Model. Employing a qualitative descriptive approach, the research describes the dynamics of women’s empowerment based on data gathered through purposive sampling involving Muslim women entrepreneurs, community leaders, and supporting institutions. Data were collected through semi-structured interviews, observation, and documentation, and analyzed using thematic categorization aligned with the components of social value, civil society, innovation, and economic activity. The findings reveal significant positive impacts at the individual, household, and community levels, including increased financial independence (social value), expanded access to training and business capital supported by local networks (civil society), adoption of digital tools and creative business practices (innovation), and enhanced household income and poverty reduction through women’s active involvement in production and management (economic activity). Overall, the study demonstrates that the emping-melinjo industry serves as an effective vehicle for advancing women’s economic empowerment, strengthening family welfare, and promoting gender-inclusive economic development within rural communities.